Curriculum and Learning for Climate Action : Toward an SDG 4.7 Roadmap for Systems Change - Iyengar, Radhika; Kwauk, Christina T. (IBE on curriculum, learning, and assessment ;, 2021)
"The global education community, guided for decades by the concept of Education for Sustainable Development, has done little to support the radical transformation of education systems needed to respond to climate change. Part of this inertia rests in five roadblocks to quality education identified in a Brookings report, and about which stakeholders from the fields of ESD, GCED, GE, and HR education came together in April 2020 to begin discussing ways of addressing. This edited volume picks up that conversation by laying out elements of a shared vision, or roadmap, for the global education sector in climate action. The volume includes perspectives that span multiple continents, disciplines, and positionalities within the education system - from policymakers to teachers to youth. It curates exiting literature, surfaces in-depth case studies, and presents overviews of conceptual frameworks on a diverse range of topics relating to systems transformation, monitoring and accountability mechanisms, lessons from the field, teacher support, as well as activism and advocacy by students. Curriculum and Learning for Climate Action: Toward an SDG 4.7 Roadmap for Systems Change offers researchers, practitioners, donors, and decisionmakers insights into entry points for education systems change needed to reorient our relationship with our planetary systems"--